Вы находитесь на странице: 1из 3

# 2 x + y +8 z=−1

1.
[ x− y+ z =−2
3 x −2 y −2 z=2 ]
Let 2 x+ y + 8 z=−1 be eq. 1

x− y + z=−2 be eq. 2
3 x−2 y−2 x=2 be eq. 3

## Add eq. 1 and eq. 2

2 x+ y + 8 z=−1
¿
----------------------------------------
3 x+ 9 z=−3
or
x +3 z=−1 (eq. 4)

## −2( x− y + z=−2)  −2 x−2 y+ 2 z=−4

3 x−2 y−2 z=2
------------------------------------
x−4 z=6 (eq. 5)

## −1( x +3 z=−1)  −x−3 z=1

x−4 z=6
---------------------------------
−7 z=7
z=−1
Substitute z=−1 in eq. 4

x +3 z=−1
x +3 (−1 )=−1
x−3=−1
x=−1+3
x=2

## Substitute x=2 and z=−1 in eq. 2

x− y + z=−2
2− y+ (−1 )=−2
2− y−1=−2
1− y =−2
− y=−2−1
− y=−3
y=3
x + z=1(eq . 1)
2.
[ 2 x + y−z =−3(eq .2)
x+ 2 y−z =−1(eq . 3) ]
Add eq. 1 an eq. 2
x + z=1
2 x+ y −z=−3
---------------------------------------
3 x+ y=−2 (eq. 4)

## Add eq. 1 and eq. 3

x + z=1
x +2 y −z=−1
----------------------------------------
2 x+2 y=0
or
x + y=0 (eq. 5)

## −1(3 x + y=−2)  −3 x− y=2

x + y=0
-------------------------
−2 x=2
x=−1
Substitute x in eq. 1
x + z=1
−1+ z=1
z=1+1
z=2

## Substitute x and z in eq. 3

x +2 y −z=−1
−1+2 y−( 2 )=−1
−3+2 y=−1
2 y=−1+3
2 y=2
y=1
3. System has infinite solution

4. No solution